Association Among Lower Urinary Tract Symptoms, Erectile Function, and Sexual Satisfaction: Results from the Brazil LUTS Study - Cristiano Mendes Gomes, MD, PhD; Marcio Augusto Averbeck, MD, MSc, PhD; Mitti Koyama; Roberto Soler, MD, PhD (Sexual Medicine, 2020)
Introduction: Lower urinary tract symptoms (LUTS) affect ≥60% of adult men and are associated with erectile dysfunction (ED) and sexual dissatisfaction. Aim: The aim of this study was to evaluate the relationship among male LUTS, ED, and sexual satisfaction. Methods: This was a secondary analysis of the Brazil LUTS study, a cross-sectional, epidemiological survey conducted by telephone interview in 5 cities in Brazil. This analysis included men aged ≥40 years. Main Outcome Measure: LUTS were identified using International Continence Society definitions. LUTS severity was assessed using the International Prostate Symptom Score questionnaire. Erectile function was assessed using the International Index of Erectile Function-5 (IIEF-5) questionnaire and sexual satisfaction was rated on a 5-point scale. Results: 2,433 men participated in the study. Of 2,183 men reporting data on LUTS, 873 (40%) had LUTS “about half the time” or more. The prevalence of ED and sexual dissatisfaction was 14.4% and 7.8%, respectively. The proportion of men reporting ED and sexual dissatisfaction was higher among men with LUTS (24.6% and 13.8%, respectively) than men without LUTS (8.7% and 4.5%, respectively; P < .001). LUTS severity was negatively correlated with IIEF-5 scores (r = –0.199; P < .001); we estimated a 0.431-point decrease in IIEF-5 score per 3-point increase in International Prostate Symptom Score. Increased age and the presence of LUTS were associated with a greater chance of ED and sexual dissatisfaction; depression/anxiety and diabetes were associated with a greater chance of sexual dissatisfaction only. Among men with LUTS, urgency with fear of leaking, urgency urinary incontinence, and nocturnal enuresis were associated with a greater chance of ED, whereas slow stream and urgency urinary incontinence were associated with a greater chance of sexual dissatisfaction. Conclusion: These results demonstrate that the presence of LUTS is associated with an increased chance of ED and sexual dissatisfaction in Brazilian men and reinforce the importance of a comprehensive assessment of these conditions.Gomes CM, Averbeck MA, Koyama M, et al. Association Among Lower Urinary Tract Symptoms, Erectile Function, and Sexual Satisfaction: Results from the Brazil LUTS Study. Sex Med 2019;8:45–56. Key Words: Erectile Dysfunction, Lower Urinary Tract Symptoms, Men, Prevalence, Sexual Satisfaction